Палеоботанічні знахідки з Білгорода Київського (за результатами археологічних досліджень 1972 та 1976 рр.) - Пашкевич, Г.О.; Непомящих, В.Ю. (Археологія і давня історія України, 2013)
У вітчизняній археології залишається актуальним дослідження та введення у науковий обіг археологічних матеріалів, що комплектують фондові колекції. Одну з них репрезентують матеріали, здобуті під час досліджень Білгорода Київського під керівництвом професора Г.Г. Мезенцевої. Серед різноманітних знахідок привертають увагу палеоетноботанічні рештки. Исследование Белгорода Киевского, как памятника национального значения, имеет целью освещение проблемных вопросов, введение в научный оборот неопубликованных археологических материалов, полученных во время систематических исследований с 1966 по 1976 гг., проведенных под руководством профессора Г.Г. Мезенцевой. Полученные данные дополняют количество пунктов на территории древнерусского государства, на которых зафиксировано преобладание зерновок ржи по сравнению с другими растениями. This research on Bilgorod Kyivs’kyi, as a monument of national importance, concerns issues on inputting in scientific use the unpublished archaeological material obtained during systematic studies from 1966 to 1976, conducted under the direction of Professor Mezentsevа. The accumulated material is a large number of findings from the collection stored in the Department of Archaeology and Museology Kyiv National Taras Shevchenko University. Among the array of diverse material charred remains caryopsides crops is being retained. The analysis of the caryopsides structure gave an interesting result, in particular, it was found that part of them were rye remains and a minor amount were cereal residues. This study revealed what crops were grown and consumed by Old Rus population of chronicle mentioned Bilgorod Kyivs’kyi.